The Role of Cosmetology in an Effective Treatment of Rosacea: A Narrative Review - Sobkowska D; Szałapska A; Pawlaczyk M; Urbańska M; Micek I; Wróblewska-Kończalik K; Sobkowska J; Jałowska M; Gornowicz-Porowska J (Dove Medical Press, 2023)
Daria Sobkowska,1 Aleksandra Szałapska,1 Mariola Pawlaczyk,1 Maria Urbańska,1 Iwona Micek,1 Katarzyna Wróblewska-Kończalik,2 Julia Sobkowska,3 Magdalena Jałowska,4 Justyna Gornowicz-Porowska1 1Department and Division of Practical Cosmetology and Prevention of Skin Diseases, Poznan University of Medical Sciences, Poznan, 60-806, Poland; 2Kolasinski Clinic, Swarzedz, 62-020, Poland; 3Medical Centre Bonus 2001, Skorzewo, 60-185, Poland; 4Department of Dermatology, Poznan University of Medical Sciences, Poznan, 60-355, PolandCorrespondence: Daria Sobkowska, Poznan University of Medical Sciences, 3 Rokietnicka Street, Poznań, 60-806, Poland, Tel +48 61 848-04-75, Email daria.sobkowska@gmail.comAbstract: Rosacea is a chronic inflammatory facial skin disease usually occurring in middle-aged patients. It manifests itself as an inflammatory condition with perivascular infiltrate, dilated blood vessels, lymphoedema, hyperplasia of sebaceous glands, and disorders of connective tissue structures brought on by fibrosis. Rosacea is characterized by multifactorial inflammatory mechanisms, and therefore it requires an interdisciplinary approach including adequate skin care, topical and/or systemic therapy, and physical modalities to successfully treat the various symptoms and disease subtypes. However, data regarding the possible role of cosmetologists in rosacea remains scanty and equivocal. The objectives of cosmetology therapy include restoration and regeneration, anti-inflammatory effects, the strengthening of blood vessels and regulation of their permeability, and the regulation of keratinization. Vascular abnormalities can be targeted with specific light and laser devices. Therefore, the present paper aims to review the latest advances and summarize different aspects concerning skin care in rosacea. Particular attention has been paid to the co-operation of cosmetologists with other specialists in order to bring about the interdisciplinary management of rosacea. It is also important to keep in mind that it is usually necessary to combine various methods of treatment, as this approach is more effective than monotherapy for attaining satisfactory cosmetic results in rosacea patients.Keywords: erythema, telangiectases, skin care, therapy, patient, cosmetologist